Bahasa Inggris - Destriana Kurniawati; Ahmad Fauzi; Rini Budiharti; Fairusy F Haryani (Postgraduate, University of Mataram, 2023)
The research aims to find out whether or not there are: differences in the impact of the use of learning models discovery learning and problem-based learning supported by media Moodle on cognitive abilities; differences in the influence of students with high and low science process skills on cognitional capabilities; and interactions between learning models discovery learning and problem-based learning with the level of skills of science processes against cognitives on sound wave materials with the research subject being students of class XI SMAN 1 Surakarta teaching 2022–2023. The method used is the experimental method with a 2x2 factorial design. The data collection techniques used are the science process skills lift and the cognitive ability test of the learners. The data obtained was then analyzed using a two-way ANAVA test with cell frequencies not equal to the conclusion. It can be concluded that: there are differences in the impact of the use of discovery learning and problem-based learning supported by Moodle on cognitive abilities (Fobs = 18.606 > F0.05;1;67 = 3.98); there is a difference in the influence of learners who have high science process skills and low science process abilities on cognition abilities (Fobs = 15.65 > F0.05;1;67 = 3.98); and there is no interaction between the influences of learning models using discovery learning and problem-based learning in cognition (Fobs = 3.514 < F0.05;1;67 = 3.98).